Parenthood: o nascimento do primeiro filho e as dinâmicas de consumo sustentável em eventos de transição - Fernandes, Andreza Cristina de Sousa (2022)
Adult consumer socialization is comprised of transition events that trigger different types of behaviors, mainly related to consumption. This approach suggests that consumption is learned through interaction with external sources, referred to as socialization agents, that is, people or groups capable of influencing emotions, attitudes and behaviors. In addition to the influence of these agents, transitory events are perceived as windows of opportunity for people to have sustainable consumption, such as parenting, understood as a transitory event in life that leads the person to assume other social roles from birth. of the first child. Thus, most of these changes that occur still do not have a natural influence on pro-environmental matters, which culminates in the need to understand the phenomenon in a broader context of the transition to parenthood, approaching the father and mother. In such circumstances, in this research, the general objective is to analyze how the dynamics of consumption occur in moments of transition from parenthood. Data collection took place online, through 15 in-depth interviews, with the help of the Zoom and Google Meet platforms, in addition to netnographic data collected on Instagram and on the Baby Center Brasil website. Each interview conducted was discussed and analyzed separately, before being aggregated as a whole, through content analysis. The results indicate that the birth of the first child causes changes in the family economy, in behavioral, structural aspects and in the parents' routine, in addition to provoking different types of more sustainable behaviors, such as the use of ecological diapers, the use of used products (frugality ) and the consumption of healthy (organic) and less sustainable foods, such as the use of disposable diapers, the purchase of a vehicle and the greater expenditure of resources. In addition to these findings, it was evidenced that the transitional event of parenting does not occur in isolation, because, before the birth of the first child, still during pregnancy, other simultaneous transitions may occur, such as: the pandemic, moving to a place of residence, changing jobs and marriage, as well as being influenced by a multitude of internal and external sources.